2009
DOI: 10.1590/s1679-62252009000100006
|View full text |Cite
|
Sign up to set email alerts
|

The role of vegetated areas on fish assemblage of the Paraná River floodplain: effects of different hydrological conditions

Abstract: In this paper, we analyze the changes in composition and abundance of fish assemblages in seven vegetated floodplain wetlands with different connectivity across different hydrologic conditions: after a prolonged connection of the floodplain with the main channel, during receding water, and after a prolonged isolation. We also investigated the size and abundance of large-sized migratory species found in these wetlands and the food resources exploited by the dominant fish. Fishes were captured by diurnal seining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 18 publications
(17 reference statements)
0
26
0
3
Order By: Relevance
“…In floodplain aquatic environments, studies aiming to find spatial or temporal patterns in response to environmental variations indicated that fish assemblages are associated with macrophyte cover, habitat complexity and depth of water bodies (Mourão et al, 1988;Petry et al, 2003;Neiff et al, 2009;Maltchik et al, 2010), among other factors. Assemblages can also differ spatially because the hydrological connectivity among the different parts of the floodplain is limited by the distance between ponds and river channel (Pouilly and Rodríguez, 2003), and by the isolation time of the ponds (Súarez et al, 2001(Súarez et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…In floodplain aquatic environments, studies aiming to find spatial or temporal patterns in response to environmental variations indicated that fish assemblages are associated with macrophyte cover, habitat complexity and depth of water bodies (Mourão et al, 1988;Petry et al, 2003;Neiff et al, 2009;Maltchik et al, 2010), among other factors. Assemblages can also differ spatially because the hydrological connectivity among the different parts of the floodplain is limited by the distance between ponds and river channel (Pouilly and Rodríguez, 2003), and by the isolation time of the ponds (Súarez et al, 2001(Súarez et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they provide refuge from predators to young and small adult fish (Meschiatti et al, 2000;Agostinho et al, 2003Agostinho et al, , 2007Neiff et al, 2009). Thus, the high complexity provided by the presence of macrophytes can promote higher fish diversity, abundance and species richness (Petry et al, 2003;Pelicice et al, 2005;Agostinho et al, 2007;Dibble and Pelicice, 2010), influencing the fish assemblage structure of littoral habitats.…”
Section: Introductionmentioning
confidence: 99%
“…These affect biodiversity and a range of processes such as fish reproduction and predation (Pusey & Arthington, 2003). At the same time, aquatic plants increase the spatial complexity of these ecosystems, favoring the presence of numerous fish species (Pelicice et al, 2005;Willis et al, 2005;Neiff et al, 2009;Thomaz & Cunha 2010). The effect of flood cycles on the structure of aquatic communities (Junk & Wantzen, 2004;Neiff et al, 2008Neiff et al, , 2009) is attenuated through the use of floating aquatic vegetation by the fish in the littoral area of the Ayapel Swamp Complex (ASC).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, aquatic plants increase the spatial complexity of these ecosystems, favoring the presence of numerous fish species (Pelicice et al, 2005;Willis et al, 2005;Neiff et al, 2009;Thomaz & Cunha 2010). The effect of flood cycles on the structure of aquatic communities (Junk & Wantzen, 2004;Neiff et al, 2008Neiff et al, , 2009) is attenuated through the use of floating aquatic vegetation by the fish in the littoral area of the Ayapel Swamp Complex (ASC). This biotope acts as a refuge, nursery and storage of resources coming from detritus, periphyton, and macro and micro invertebrates (Poi de Neiff & Neiff, 2006;Sánchez-Botero et al, 2007;Montoya-Moreno & Aguirre-Ramírez, 2009;Villabona-González et al, 2011).…”
Section: Introductionmentioning
confidence: 99%